Oral Beta-blocker in Problematic Infantile Hemangioma. Issue 5 (18th May 2021) - AlHasan, Rashed N.; Arabiyat, Lamees; Ammar, Hamad M.; Louri, Nayef A.
Abstract : Summary: One of the most common benign vascular endothelial tumors is infantile hemangioma. These lesions are commonly found in the head and neck, and sometimes it is a challenge to decide the method of treatment if the lesions are problematic hemangiomas, interfering with function or aesthetic appearance. This study reports a case of girl aged 3 years, 7 months, diagnosed with periorbital infantile hemangioma that was successfully treated with oral propranolol in specific doses and gradual tapering off dose. The patient had marked involution of the lesion with no significant side effects after starting her treatment at the age of 4 months, for a total of 13 months with no reported rebound growth after almost 2 years since the termination of treatment. Oral beta-blockers can be used safely in treatment of problematic infantile hemangioma as a single modality, without any surgical intervention.